Trends of drug licensing in China: From bring-in to go-global - Yale Jiang; Guo Zhao; Linlin Jia; Cheng Li; Xin Wang; Jing Cai; Huiyao Huang; Shuhang Wang; Ning Li (Pharmacological Research)
Global medicine R&D has shown a stabilized trend after fleeting prosperity lately. Despite of discouraging whole picture, the role of China in cross-border out-licensing activities of medical therapeutics keeps rising, which started since 2020 and further boosted in 2023. A holistic analysis of drug and technology licensing, involving Chinese enterprises from 2019 to 2023, revealed 807 license-in deals and 401 license-out deals. In-licensing showed a decreasing trend, while out-licensing was the opposite. Increasing ingenuity of Chinese products has led to a shift from an import-oriented to an export-oriented situation, such as antibody-drug-conjugates, and cell/gene therapies. With supportive policies of Chinese government, southeast Asia is becoming an important downstream market for out-licensed drugs. Biotech innovators are emerging as a dominant force with core innovation capacity. China is embracing international collaboration by showing favorable markets and high-level innovative products.